2014
DOI: 10.1136/bmjopen-2014-005549
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of healthcare professionals’ attitudes towards family involvement in safety-relevant behaviours: a cross-sectional factorial survey study

Abstract: ObjectivesTo investigate predictors of healthcare professionals’ (HCPs) attitudes towards family involvement in safety-relevant behaviours.DesignA cross-sectional fractional factorial survey that assessed HCPs’ attitudes towards family involvement in two error scenarios relating to hand hygiene and medication safety. Each survey comprised two randomised vignettes that described the potential error, how the family member communicated with the HCP about the error and how the HCP responded to the family member’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Davis demonstrated that only 41% of providers felt that family member involvement would have a positive effect on the family member-provider relationship. 13 Similarly, Kim found that only 26% of physicians and 31% of nurses supported patient participation. 14 In Julian’s survey of healthcare providers, the major reasons providers did not support patient empowerment were providers did not feel it was the patient’s responsibility, the patient may not see that the provider previously cleansed their hands, and reminders from the patient were embarrassing or inappropriate.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Davis demonstrated that only 41% of providers felt that family member involvement would have a positive effect on the family member-provider relationship. 13 Similarly, Kim found that only 26% of physicians and 31% of nurses supported patient participation. 14 In Julian’s survey of healthcare providers, the major reasons providers did not support patient empowerment were providers did not feel it was the patient’s responsibility, the patient may not see that the provider previously cleansed their hands, and reminders from the patient were embarrassing or inappropriate.…”
Section: Discussionmentioning
confidence: 97%
“…Healthcare workers have expressed concern that patient empowerment will have a negative impact on the patient-physician relationship. 13, 14 …”
Section: Introductionmentioning
confidence: 99%
“…Studies have tried to cover family involvement from the perspectives of healthcare professionals (HCPs; Davis et al . ), patients (Lin et al . ) and family members (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…More forethought considering their feedback should be put into planning educational activities and materials. As clinicians responsible for patient and family education, nurses should encourage and empower family members to play significant roles in optimizing IP efforts (Davis, Savvopoulou, Shergill, Shergill, & Schwappach, 2014). …”
Section: Discussionmentioning
confidence: 99%